PURCHASING DECISION MODEL AND CUSTOMER SATISFACTION (MARKETING MANAGEMENT LITERATURE REVIEW) - Muhammad Reza Putra; Ridho Rafqi Ilhamalimy (Dinasti International Journal of Management Science, 2021)
The purpose of writing a Literature Review is to determine the effect of variable product quality and brand image on purchasing decision variables and consumer satisfaction. With qualitative methods and Library Research. The results showed that product quality has an effect on purchasing decisions, product quality has an effect on customer satisfaction, brand image has an effect on purchasing decisions, brand image has an effect on customer satisfaction and purchasing decisions have an effect on customer satisfaction.